2012
DOI: 10.1002/dama.201200524
|View full text |Cite
|
Sign up to set email alerts
|

Druckfestigkeit von Ziegelmauerwerk – aktuelle Auswertungen zur Festlegung von charakteristischen Mauerwerkdruckfestigkeiten in DIN EN 1996

Abstract: Das Institut für Bauforschung der RWTH Aachen (ibac) hat im Auftrag der Arbeitsgemeinschaft Mauerziegel in mehreren Projekten die in Deutschland vorliegenden Versuchsergebnisse zur Druckfestigkeit von Ziegelmauerwerk auf der Grundlage der aktuell definierten Randbedingungen neu ausgewertet. Für Hochlochziegel HLzB mit Normalmauermörtel zeigte die Auswertung rund 10 % höhere Werte als bislang in DIN 1053 definiert. Für Planziegel nach E DIN 105‐6:2011‐04 wurden erstmalig Werte vorgeschlagen, die die Basis für d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Based on typical unit and mortar strengths of f b = 25 N/mm 2 and f j = 5 N/mm 2 , respectively, a characteristic masonry strength of Fig. 6 Uniaxial stress-strain relationship for the expanded units f ma,k = 8.1 N/mm 2 is obtained according to [27], corresponding to a mean value of f ma,m = 9.1 N/mm 2 (assuming f ma,k = 0.8 f ma,m [28]). Hence, the normalised unit tensile strength is f bt /f ma = 0.11.…”
Section: Materials Modellingmentioning
confidence: 99%
“…Based on typical unit and mortar strengths of f b = 25 N/mm 2 and f j = 5 N/mm 2 , respectively, a characteristic masonry strength of Fig. 6 Uniaxial stress-strain relationship for the expanded units f ma,k = 8.1 N/mm 2 is obtained according to [27], corresponding to a mean value of f ma,m = 9.1 N/mm 2 (assuming f ma,k = 0.8 f ma,m [28]). Hence, the normalised unit tensile strength is f bt /f ma = 0.11.…”
Section: Materials Modellingmentioning
confidence: 99%
“…Die im Eurocode 6 angegebenen Werte für die charakteristische Druckfestigkeit von Mauerwerk gelten für neu zu errichtendes Mauerwerk aus Normsteinen und den entsprechenden Mörteln (s. auch [5] und [6]). Für Bestandsbauten empfiehlt es sich, eine konkrete Bewertung durch Beprobung oder eine Umrechnung auf die charakteristische Festigkeit vorzunehmen.…”
Section: Introductionunclassified
“…Jäger and Pech (2014) made discussion on this equation regarding the methodology and underlying mathematical basis for the anticipated update and adaptation of Eurocode 6 (CEN 1996), comparing with equations presented by other researchers. For instance, referring to Brameshuber et al (2012), the authors suggested that the material factor, K is to be reduced by 80% for better estimation of characteristic compressive strength of masonry. Geoff ratio, Young's modulus and the tensile strength of units.…”
Section: 1111mentioning
confidence: 99%